Elemental and Infrared Characterization of Contaminants in Second-Hand Cotton Garments From Flea Markets In Valencia City, Bukidnon, Philippines - Marilou Auxtero Pedroso Butanas; Bienvenido Masirin Butanas Jr. (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2018)
The use of Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) characterizations have been indispensable techniques in distinguishing purity of the samples. These techniques give spectra that will be used to analyze the composition, morphology, purity, among others, of the material. One of its interesting applications is to assess elemental and chemical contaminations on second hand clothing. In this study, second hand (Ukay-Ukay) cotton garments from selected flea market sites in Valencia City, Bukidnon, Philippines were examined quantitatively for microbial and chemical contaminations by using FTIR, SEM, and EDX. The FTIR results obtained in both sites showed broad peaks at ~3336 cm-1 attributed to OH functional group, and absorption peaks at 2901.30 cm-1 associated to C-H bond, 1159.70 cm-1, 1107.44 cm-1 and 1053.82 cm-1 attributed to the stretches of CO bond. All of them were characteristics of cotton material. We observed degradation of the cotton material on both sites evident in the decreasing intensity of OH stretching (at peaks around ~3334 cm -1 [site A] and ~3332 cm -1 [site B]) and C-O stretching (around ~1500-1700 cm-1). These were due to the presence of microorganisms such as fungi (e.g. Aspergillus species). The degradation was also observed in the SEM results. Furthermore, peaks related to carboxylate contaminants were observed in both sites around ~1600 1800 cm-1 that may be caused by the exposure of the cotton garments in hydrochloric acid (HCl). In general, the characterization results on both sites indicated traces of microorganisms and that the second-hand cotton clothes were contaminated by hazardous chemicals.